Screening of some Medicinal Plants used in Nepalese Traditional Medicine against Enteric Bacteria - Bajracharya, Anup Muni; Yami, Kayo Devi; Prasai, Tista; Basnyat, Shital Raj; Lekhak, Binod (Scientific World, 2010)
Antibacterial properties of ethanolic extracts of 8 medicinal plants used in Nepal to treat gastrointestinal disorders were tested against ten different species of enteropathogenic bacteria: Escherichia coli, Klebsiella spp, Citrobacter spp, Enterobacter spp, Salmonella typhi, Salmonella paratyphi, Shigella spp, Proteus vulgaris, Proteus mirabilis and Pseudomonas spp. Among the selected medicinal plants: Punica granatum, Woodfordia fruticosa, Psidium guajava and Syzygium cumini were found effective against all enteric bacteria whereas Mimosa pudica, Acorus calamus, Aegle marmelos and Anethum sowa were found ineffective against all. The minimum bactericidal concentration (MBC) of these plant extracts found against Salmonella typhi, Salmonella paratyphi, Proteus mirabilis and Proteus vulgaris were lower (0.39-25mg/ml) so are more susceptible whereas the plants showed lethal effect against Pseudomonas spp, Citrobacter spp, Enterobacter spp, E. coli, Shigella spp. and Klebsiella spp. at MBC value of around 25-50mg/ml. Key words: Medicinal plants; Antibacterial activity; Plant extracts. DOI: 10.3126/sw.v6i6.2644 Scientific World, Vol. 6, No. 6, July 2008 107-110